THE EFFECT OF REFORMULATION TECHNIQUE TO IMPROVE STUDENTS’ WRITING ABILITY - Henny Septia Utami (IAIN Syekh Nurjati Cirebon, 2018)
The purpose of this research is to investigate whether reformulation technique gives significant effect on student’s writing ability. The design of this research is an experimental research that is classified into a randomized pretest and posttest group design. There are two groups involved in this research: experiment and control group. Those two groups are chosen based on the normality and homogenity calculations. The instrument used is writing test which is given as pretest and posttest. To ensure the validity and reliability of the instrument, it was tried out before being used and the students’ writings were scored by three raters. The data were analyzed by using T-test. The result shows that this technique gives significant effect to students’ ability in writing.